The Effect Of Listening Qur’an Recitation Therapy Towards Physiologic Outcomes Among Neonates Underwent In Neonatal Intensive Care Unit: Meta-Analysis - Wardani, Sholichah Kusuma; Hidayat, Ahmad; Dewi, Desi Dwi Siwi Atika; Suciati, Wahida Yuyun; Masdar, Mahmasoni (Universitas Islam Negeri Alauddin Makassar, 2026)
Audio stimulation, including Qur'an recitation therapy is broadly utilized within the neonatal intensive care unit (NICU). This study aimed to evaluate the effect of Qur’an recitation therapy compared with routine care on physiological outcomes among neonates admitted to the NICU. A comprehensive systematic review was conducted in PubMed, ScienceDirect, Cochrane Library, Scopus, ProQuest, and ClinicalKey, and the final search was performed on 16 October 2025 in Google Scholar to identify relevant English and Arabic studies comparing Qur’an recitation therapy with routine care. A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-analyses 2020 (PRISMA) guidelines, with search terms containing